College expectations of eighth grade students: The role of learning approaches and parent influences. (September 2019) - Kremer, Kristen P.; Huang, Jin; Vaughn, Michael G.; Maynard, Brandy R.
Abstract: The development of expectations to attend college is the first step toward future college attendance, yet its predictors are not fully understood. The current study seeks to identify individual and parent predictors of expectations for college completion among eighth grade students and examine inter-relationships between the independent variables. Data were used from the Early Childhood Longitudinal Study-Kindergarten Cohort (ECLS-K), a nationally representative and longitudinal study of 21, 260 kindergarteners. Logistic regression models were employed to predict college expectations of eighth grade students from child and parent characteristics. Youth were more likely to expect to complete college when they had greater learning approaches (OR = 1.82, 95% CI = 1.05–3.15) and higher school competence/liking (OR = 1.60, 95% CI = 1.13–2.26). Controlling for demographic covariates, the odds of students expecting to complete college were nearly four times greater for youth whose parents expected them to complete a bachelor's degree (OR = 3.82, 95% CI = 2.34–6.23), compared to parents who expected their children to complete high school or less. A generalized structural equation model was then specified to understand the inter-relationships between child's behavior, learning approaches, and reading and math abilities. Child's self-control (β = 0.57, 95% CI = 0.53–0.60) and internalizing behavior (β = −0.15, 95% CI = -0.19 - -0.12) significantly predicted learning approaches, which then predicted child's reading ability (β = 0.24, 95% CI = 0.20–0.28) and math ability (β = 0.26, 95% CI = 0.00–0.53). Future research should examine effectiveness of programs seeking to increase student learning abilities and feelings of competence. Highlights: Youth with greater learning approaches had higher college expectations. Youth who had higher school liking and competence had greater college expectations. Parents with higher expectations had children with higher college expectations.